2020
DOI: 10.1111/1471-3802.12492
|View full text |Cite
|
Sign up to set email alerts
|

Do they practise what they preach? Factors associated with teachers’ use of inclusive teaching practices among in‐service teachers

Abstract: Applying the 'theory of planned behaviour' to teachers' actions in the classroom, it can be assumed that teachers' positive attitudes towards inclusive education and high self-efficacy beliefs result in an increased use of inclusive teaching practices. However, scientific evidence for this assumption is lacking. This study aimed to investigate factors influencing teachers' use of inclusive teaching practices. In total, 221 (188 female and 33 male) Austrian in-service teachers participated. Participants filled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 42 publications
9
36
0
Order By: Relevance
“…In line with previous research, descriptive results further indicated that students reported relatively high ratings of school-wellbeing, social inclusion and academic self-concept (Alnahdi and Schwab, 2020;Schwab and Alnahdi, 2020;Zubriggen et al, 2021). However, high mean scores do not automatically imply that all students are reaching satisfying levels in their socio-emotional well-being.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In line with previous research, descriptive results further indicated that students reported relatively high ratings of school-wellbeing, social inclusion and academic self-concept (Alnahdi and Schwab, 2020;Schwab and Alnahdi, 2020;Zubriggen et al, 2021). However, high mean scores do not automatically imply that all students are reaching satisfying levels in their socio-emotional well-being.…”
Section: Discussionsupporting
confidence: 86%
“…Most research that explores the effectiveness of DI has mainly focused on investigating its impact on students' achievement. Research which analyzes the impact of DI on students' nonachievement outcomes are relatively limited (Schwab and Alnahdi, 2020). As variables such as students' school wellbeing, social inclusion and academic self-concept are also central objectives of inclusive education and education in general , it is necessary to address this research gap.…”
Section: Purpose and Research Questionmentioning
confidence: 99%
“…However, other variables like e.g., teachers' constructivist beliefs (see Pozas et al, 2020) or teachers attitudes toward inclusive education (see e.g., Schwab and Alnahdi, 2020) might be underlying factors which are not investigated within the present study.…”
Section: Discussionmentioning
confidence: 95%
“…Empirical studies (Hellmich, Löper, and Görel 2019;Schwab and Alnahdi 2020) indicated that teachers' beliefs interact with their practices in complex ways; however, little is known about the nature and the extent of this interaction (Farrell and Ives 2015). Two main trends illustrating the relationship were identified.…”
Section: Teachers' Beliefs and Practicesmentioning
confidence: 99%